(untitled) (Construction Economics and Building, 2012)
Substantial changes, not only in the demographic composition of the Australian workforce, but also,in the roles and expectations of men and women, have led to organisational and employee attempts to reconcile work and non-work demands. Research suggests that when work-family balance practices are introduced they can greatly enhance organisational efficency. However factors embedded in the organisational culture can undermine these policies rendering them ineffective. This quantitative study examined the relationship between the perceptions of a supportive work culture and some work and non-work experiences of Australian male civil engineers. The research investigated the prevalence of organisational values supportive of work-life balances as well as the level of work-family conflict perceived by those engineers. This paper reports some initial results of the study. These indicated that male civil engineers experienced moderate levels of work-family conflict but do not perceive their organisations to be very supportive of employee nneeds to balance work and personal life. However those that reported a supportive work environment also reported higher levels of organisational commitment, greater job and life satisfaction as well as lower level of work-family conflict and lower intentions to quit. The implications of the findings for organisations employing civil engineers are discussed.